Hormones and reproduction of vertebrates : volume 5: mammals - Lopez, Kristin H.; Norris, David O. (Elsevier ; Academic Press, 2011)
Provides a coordinated description of reproductive basics in each group of vertebrates. This title features terminology to reduce confusion where multiple names exist in the literature, and a comprehensive glossary of these terms and their alternative names is provided. It is suitable for research scientists working on vertebrate hormones